Transforming growth factor-β superfamily members as potential biomarkers for adolescent major depressive disorder - Wang, Xiaolan; Kong, Yiting; Xiang, Jingyue; Jiang, Zhenghao; Wang, Yijia; Chen, Xiaorong; Wan, Liyang; Hong, Su; Kuang, Li (Frontiers in Psychiatry, 2025)
BackgroundGrowing evidence implicates the transforming growth factor-β (TGF-β) superfamily in neurodevelopment and immunoregulatory processes, with several members associated with depression in adults. However, the relationship between specific TGF-β superfamily members and adolescent major depressive disorder (MDD) remains poorly understood. This study aimed to evaluate whether specific TGF-β superfamily members could serve as biomarkers for adolescent MDD.MethodsIn this cross-sectional study, 180 adolescents were enrolled,including individuals diagnosed with MDD and healthy controls (HC). Depressive symptoms were assessed using the 17-item Hamilton Depression Rating Scale (HAMD-17). Serum concentrations of transforming growth factor-β1 (TGF-β1),growth differentiation factor 11 (GDF11), and growth differentiation factor 15 (GDF15), were quantified via enzyme-linked immunosorbent assay (ELISA). Demographic and clinical characteristics were analyzed.Correlation and multiple linear regression analyses were performed to explore associations between serum TGF-β superfamily levels and depression severity. Furthermore, receiver operating characteristic (ROC) curve analysis was used to assess the diagnostic potential of these TGF-β superfamily members in MDD.ResultsCompared with healthy controls, the MDD group exhibited significantly lower serum levels of TGF-β1 and GDF11,and higher levels of GDF15 (all p< 0.05). Correlation analysis revealed that serum TGF-β1 and GDF11 were negatively associated with depression severity, while GDF15 levels showed a positive correlation. All three molecules demonstrated strong diagnostic potential for MDD. Combination of these three proteins demonstrated much better diagnostic effectiveness.ConclusionsSerum TGF-β1, GDF11, and GDF15 levels may serve as promising biomarkers for adolescent MDD, offering potential utility in identifying disease susceptibility. These findings highlight the TGF-β superfamily’s role in adolescent depression and warrant further mechanistic investigation.